2014
DOI: 10.1684/epd.2014.0680
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal dysembryoplastic neuroepithelial tumours associated with refractory epilepsy

Abstract: Dysembryoplastic neuroepithelial tumours (DNET) are a common cause of tumour‐associated epilepsy, and are usually located in the temporal lobes. We present a case of multifocal DNETs in both infra‐ and supra‐tentorial locations, in a 23‐year‐old man with a coincident Type I Chiari malformation, presenting with medically refractory focal seizures. The extensive anatomical distribution of the lesions suggests a genetic component in their tumourigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, there are only seven reports of multifocal DNT in the English literature. [3][4][5][6][7][8][9][10] The present case was mostly cortical with no prominent mass effect and almost unchanged in size and configuration in MRI studies during two years follow up. DNTs are usually cortical tumors with neither mass journals.sbmu.ac.ir/Neuroscience http effect nor significant peritumoral edema, and these are essential differentiating factors between DNTs and diffuse infiltrating gliomas.…”
Section: Discussionsupporting
confidence: 47%
“…To the best of our knowledge, there are only seven reports of multifocal DNT in the English literature. [3][4][5][6][7][8][9][10] The present case was mostly cortical with no prominent mass effect and almost unchanged in size and configuration in MRI studies during two years follow up. DNTs are usually cortical tumors with neither mass journals.sbmu.ac.ir/Neuroscience http effect nor significant peritumoral edema, and these are essential differentiating factors between DNTs and diffuse infiltrating gliomas.…”
Section: Discussionsupporting
confidence: 47%
“…Multifocal and cerebellar DNET are rare and based on our review of reported cases, there appears to be a relationship between DNET multifocality, cerebellar location, and presence of an underlying genetic syndrome. Including our patient, there have been 12 multifocal cases reported [Leung et al, ; Lellouch‐Tubiana et al, ; Whittle et al, ; Fujimoto et al, ; Krossnes et al, ; Schittenhelm et al, ; White et al, ; Krishna et al, ; Delisle et al, ; Yang et al, ], seven of which involved the cerebellum [Leung et al, ; Whittle et al, ; Fujimoto et al, ; Krossnes et al, ; Krishna et al, ; Yang et al, ]. Of the 12 multifocal cases, five patients had genetic disorders: one with Klinefelter syndrome, one with NF1, and three with NS [Lellouch‐Tubiana et al, ; Krossnes et al, ; Krishna et al, ; Delisle et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Multifocality is also an atypical presentation for DNETs, as these tumors tend to be solitary. However, there have been rare case reports of multifocal DNETs [8,[12][13][14][15][16][17], which was first described by Leung et al in 1994 [13]. Furthermore, multifocal presentation has been reported in association with hereditary conditions such as Jacob's syndrome (47,XYY) [14] or neurofibromatosis type 1 (NF1) [18].…”
Section: Discussionmentioning
confidence: 99%